Analisis Pendidikan terhadap Q.S Ali Imran Ayat 137-138 tentang Sinergisitas Iman, Ilmu, dan Akhlak - Fuad Bahrudin; Sobar Al Ghazali; Alhamuddin (UNISBA Press, 2022)
Abstract. Education as a scientific activity must be based on the principles of faith and monotheism. The Qur'an in every discussion about science (knowledge) is inseparable from the value of faith. Experts formulate educational goals to form students to have strong faith, have noble character, and have useful knowledge. As explained in the Al-Qu'an Surah Ali Imraan verses 137-138, it calls on humans to learn and take lessons and examples from the previous people. So that human beings can walk on this earth following the provisions of Allah SWT in order to avoid human groups who lie to Allah SWT. This research uses descriptive-analytical method. The collection technique uses library research by examining in depth various interpretations, books and articles related to the main research problem. From this research, it is concluded that an educator must have a synergy of faith, noble character, in order to have useful knowledge. The implications contained in the Qur'an Surah Ali Imrran Verse 137-138 are (1) So that humans can take lessons from past history, from the sunnahs of Allah that applied to humans before. (2) So that humans know the way of life that is straight and true, where the Qur'an is the one who becomes the educator and becomes the light of the way of human life. (3) In order for humans to become educators to create human beings who are faithful, knowledgeable and civilized, it is impossible for education providers alone, there must be intervention from parents/guardians of students and the community, which is very important in monitoring so that they become pioneers of education at home and in their respective environments each. Abstrak. Pendidikan sebagai aktivitas ilmu pengetahuan harus dilandasi prinsip keimanan dan ketauhidan. Al-Qur’an dalam setiap pembicaraanya tentang ilmu (pengetahuan) tidak terlepas dari nilai keimanan. Para ahli merumuskan tujuan pendidikan untuk membentuk para peserta didik memiliki keimanan yang kuat, berakhlak mulia, dan memiliki ilmu yang bermanfaat. Sebagaimana di jelaskan di dalam Al-Qu’'an surat Ali Imraan ayat 137-138, menyeru kepada manusia agar belajar dan mengambil hikmah dansuri tauladan dari umat terdahulu. Aagar umah manusian dapat berjalan di muka bumi ini mengikuti ketentuan-ketentuan Allah SWT agar terhindar dari golongan manusia yang berdusta kepada SWT. penelitian ini menggunakan Metode deskriptif-analitis, Teknik pengumpulan menggunakan kepustakaan (library research) dengan mengkaji secara mendalam dari berbagai tafsir, buku dan artikel yang berhubungan dengan pokok masalah penelitian. Dari penelitian ini, diperoleh simbpulan bahwa seorang pendidik harus memiliki sinergitas keimanan, berakhlak mulia, agar mempunyai lilmu yang bermanfaat. Implikasi yang terdapat dalam Al-Qur’an Surat Ali Imrran Ayat 137-138 adalah (1) Agar manusia bisa mengambil pelajaran dari sejarah masa lalu, dari sunnah-sunnah Allah yang berlaku pada manusia sebelumnya. (2) Agar manusia mengetahui jalan hidup yang lurus dan benar, dimana Al-Qur’an lah yang menjadi pendidik dan menjadi penerang jalan hidup manusia. (3) Agar manusia dapat menjadi pendidik untuk mewujudkan manusia yang beriman, berilmu dan beradab tidak mungkin dilaksanakan oleh penyelenggara pendidikan semata, harus ada campur tangan orang tua/wali murid serta masyarakat sangat penting dalam memonitoring hingga menjadi pelopor pendidikan di rumah dan di lingkungan masing-masing.